TerraNeo: Towards a Sustainable Exascale Framework for Earth Mantle Convection - Rüde, Ulrich (CoSaS 2018: International Symposium on Computational Science at Scale, 2018)
The talk summarizes some driving development on the road to exascale. It presents recent results in the TerraNeo project aimed at developing an efficient parallel software framework for Earth Mantle convection.<br